1976
DOI: 10.1111/j.1651-2227.1976.tb04920.x
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Vein Catheterization and Portal Hypertension

Abstract: Portal hypertension is a rarely encountered late complication of umbilical vein catheterization. A survey of the 38 cases previously published is presented together with an additional case report. It is concluded that catheterization for more than 2 days carries an increased risk of thrombosis, and that umbilical artery catheterization should be preferred in the majority of cases due to a reduced risk of complications. The correct position of the catheter tip must always be controlled by fluoroscopy or X-ray. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

1978
1978
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 17 publications
0
14
0
1
Order By: Relevance
“…This study and other case reports demonstrate the importance of long-term follow-up of infants with PVT. 2,19 Atrophy of the left hepatic lobe, previously considered a normal variant, 20,21 was diagnosed in 30 infants. A correlation between hepatic lobar atrophy and ipsilateral portal vein obstruction has been reported in adults.…”
Section: Discussionmentioning
confidence: 99%
“…This study and other case reports demonstrate the importance of long-term follow-up of infants with PVT. 2,19 Atrophy of the left hepatic lobe, previously considered a normal variant, 20,21 was diagnosed in 30 infants. A correlation between hepatic lobar atrophy and ipsilateral portal vein obstruction has been reported in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Portal vein thrombosis (PVT) as a manifestation of VTE may occur in children with underlying risk factors such as malignancy, inherited thrombophilia, infections, splenectomy, sickle cell disease, chemotherapy, or the presence of antiphospholipid antibodies. Furthermore, it can present as a complication following pediatric liver transplantation …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it can present as a complication following pediatric liver transplantation. [2][3][4][5][6][7][8][9] We report a case of an idiopathic portal vein thrombosis in a child, presenting with portal hypertension, esophageal and rectal varices, splenomegaly, and gastrointestinal bleeding with unconfirmed etiology in known medical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to minimize complications associated with UVCs focus on prompt removal after a short period of use. 67 The Centers for Disease Control and Prevention currently recommend use of UVCs be limited to 14 days. 68 A randomized trial compared long-term UVC use (up to 28 days) with short-term (7 to 10 days) use followed by peripheral CVL placement; investigators found that in the short-term group, 9% developed thrombi with 4% being clinically significant compared with 13 and 7%, respectively, in the long-term group.…”
Section: Venous Thrombosismentioning
confidence: 99%